1985
DOI: 10.1021/ja00308a032
|View full text |Cite
|
Sign up to set email alerts
|

The structure and stability of the 10-F-2 trifluoride ion, a compound of a hypervalent first row element

Abstract: Well correlated ab initio electornic structure calculations have been used to investigate the structure of the trifluoride ion. It is calculated to be stable with respect to F and Fz by about 11 kcal/mol. While this represents a relatively weak bonding of F to F2 to form F<, a significant interaction is evidenced by a 0.3-A lengthening of the F2 bond (from 1.41 to 1.70 %.) upon forming the Dmk F3-. This lengthening of the F-F bond distance decreases the repulsive *-type interactions of the unshared electron pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 2 publications
2
39
0
Order By: Relevance
“…We also tested that the CCSD͑T͒ surface has the adequate shape in all its regions. Besides Heard et al 12 computations, there are other monoreference computations in the literature using lower levels of correlation, like the approximate CCD of Cahill et al 10 and our previous MP2 computations. 11 Both agreed in showing that the F 3 Ϫ anion is stable against its dissociation into F 2 and F Ϫ and in predicting a minimum of D ϱh symmetry.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We also tested that the CCSD͑T͒ surface has the adequate shape in all its regions. Besides Heard et al 12 computations, there are other monoreference computations in the literature using lower levels of correlation, like the approximate CCD of Cahill et al 10 and our previous MP2 computations. 11 Both agreed in showing that the F 3 Ϫ anion is stable against its dissociation into F 2 and F Ϫ and in predicting a minimum of D ϱh symmetry.…”
Section: Introductionmentioning
confidence: 88%
“…[9][10][11][12][13] Most of these computations are at the monoreference level [9][10][11][12] and only a multireference MCSCF computation 13 and a singlepoint multireference MP2 have been reported. 11 These computations have shown that a proper description of the electronic structure of the F 3 Ϫ anion is a difficult challenge, the results depending strongly on the method and basis set employed.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Using the VB method, Braïda and Hiberty showedt hat the [F 3 ] À ground state is of ap redominant three-electron bond character and the stabilityof[F 3 ] À thus origins form both the significant stability of the three-electron bond in [F 3 ] À ,w hichi sa lmost as strong as the conventional two-electron bond in F 2 ,a nd the contribution of the nonbondeds tructure. [13b] This VB view of the bondingn ature in [F 3 ] À is an alternative to the earlier interpretation within the Rundle-Pimentel model by Cahill et al [14] The advantage of VB methods in the study of polyhalogen monoanionsi st he clear chemicali nsight that thesem ethods bring aboutc hemical bonding. [23,24] In this work, the variation of the covalence in [X 3 ] À (X = Cl, Br) along with the X 2 ···X À distance will be studied by means ab initio VB theory (see the Supporting Information) as well as the BLWm ethod, which is av ariant of the VB method.…”
Section: Introductionmentioning
confidence: 87%
“…Using the VB method, Braïda and Hiberty showed that the [F 3 ] − ground state is of a predominant three‐electron bond character and the stability of [F 3 ] − thus origins form both the significant stability of the three‐electron bond in [F 3 ] − , which is almost as strong as the conventional two‐electron bond in F 2 , and the contribution of the non‐bonded structure . This VB view of the bonding nature in [F 3 ] − is an alternative to the earlier interpretation within the Rundle–Pimentel model by Cahill et al . The advantage of VB methods in the study of polyhalogen monoanions is the clear chemical insight that these methods bring about chemical bonding .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation